Enzymes in food technology (Sheffield Academic Press, 2002)
The second edition of this successful book highlights the widespread use of enzymes in food processing improvement and innovation, explaining how they bring advantages. The properties of different enzymes are linked to the physical and biochemical events that they influence in food materials and products, while these in turn are related to the key organoleptic, sensory and shelf life qualities of foods. Fully updated to reflect advances made in the field over recent years, the book also contains five new chapters.